(untitled) (Swiss Medical Weekly, 2014)
QUESTIONS UNDER STUDY: Despite various efforts to estimate cost-effectiveness of pneumococcal conjugate vaccines, only scarce information on the cost burden of paediatric community acquired pneumonia (CAP) exists. The objective of this study was to prospectively calculate direct and indirect costs associated with treatment of CAP from a society perspective in children between 2 months and 16 years of age seeking care at a tertiary hospital in Geneva, Switzerland between December 2008 and May 2010. METHODS: This cost of illness study population comprised children aged from 2 months to 16 years of age seeking care for CAP at the University Children’s Hospital Geneva from January 2008 through May 2010 (a subset of patients taken from a larger multicentre prospective cohort). Hospital-associated costs for episodes of pneumonia were computed according to the REKOLE® system. Non-hospital costs were estimated by parental interviews at baseline and follow-up on day 14. RESULTS: The overall cost for one episode of CAP was 11’258 CHF; 23’872 CHF for inpatient treatment and 1009 CHF for outpatient treatment. Severe pneumonia cases per World Health Organisation (WHO) definition used significantly more hospital resources than non-severe cases: 21’842 CHF versus 3479 CHF (p <0.0001). CONCLUSION: Childhood CAP results in a significant medical cost burden that may have been underestimated in previous cost-effectiveness analyses of pneumococcal vaccine strategies.